2021
DOI: 10.1177/1084822320983314
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics and Functional Levels of Patients With Fragility Fractures Who Accept Tele-rehabilitation as an Alternative to Face-to-face Home Rehabilitation

Abstract: There is a gap in the evidence on telerehabilitation (TR) for people with fragility fractures. It is unclear whether this group with recent falls who are often frail with cognitive changes will accept tele-rehabilitation and functional gains can be achieved using this approach. Prospective observational study of consecutive patients admitted with femoral or pelvic fracture to a hospital-based home rehabilitation service (HRS) between January and November 2017. Using tablets, multidisciplinary rehabilitation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The preference for face-to-face communication has been reported by patients in similar studies examining the use of digital health interventions by older adults. 20,21,33 However, studies examining the effectiveness of 7 Indeed, participants in our study (n=3 patients, n=4 caregivers) identified the opportunity for written instructions in the web-based application as an incentive to use, and described web-based applications as having the potential to improve overall communication with their healthcare providers (n=1 patient, n=4 caregivers). Overall, patients more frequently expressed belief statements indicating low motivation for using web-based applications than caregivers, such as not finding web-based applications important to use (n=7, 38.9%), and having no intention of using a web-based application (n=3, 16.7%).…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…The preference for face-to-face communication has been reported by patients in similar studies examining the use of digital health interventions by older adults. 20,21,33 However, studies examining the effectiveness of 7 Indeed, participants in our study (n=3 patients, n=4 caregivers) identified the opportunity for written instructions in the web-based application as an incentive to use, and described web-based applications as having the potential to improve overall communication with their healthcare providers (n=1 patient, n=4 caregivers). Overall, patients more frequently expressed belief statements indicating low motivation for using web-based applications than caregivers, such as not finding web-based applications important to use (n=7, 38.9%), and having no intention of using a web-based application (n=3, 16.7%).…”
Section: Discussionmentioning
confidence: 84%
“…The preference for face-to-face communication has been reported by patients in similar studies examining the use of digital health interventions by older adults. 20 , 21 , 33 However, studies examining the effectiveness of different modes of communication in healthcare settings, have found that verbal instructions are often remembered incorrectly, if at all, by patients. 7 Indeed, participants in our study (n=3 patients, n=4 caregivers) identified the opportunity for written instructions in the web-based application as an incentive to use, and described web-based applications as having the potential to improve overall communication with their healthcare providers (n=1 patient, n=4 caregivers).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations